Regarding Formation of the International Space Private Law - M. R. Yuzbashyan (Московский журнал международного права, 2008)
For several years international lawyers specializing in the field of the international space law are talking about formation of the international space private law. This opinion is also supported by a number of countries’ official delegations at UN COPUOS and its Legal Subcommittee. But nevertheless there is a lack of overall scientific research on this issue.It seems that international space private law could provide the most adequate legal regulation for private space activities.The author of this article defines international space private law as a set of substantive and conflict norms regulating property and personal nonproperty relations with a “foreign element” connected with space activity.International space private law is characterized by its specific subject and methods of legal regulation.Principal existing and potential legal sources of the international private space law are:• The 2001 Cape Town Convention on International Interests in Mobile Equipment and the draft Space Assets Protocol.The primary character of UN space treaties is prescribed both by the 2001 Cape Town Convention and draft Space Assets Protocol;• National space legislation (e.g. U.S, Russian, UK and Ukraine laws and etc.);• Space law cases.This article also contains a brief on legal status of subjects of the international space private law.Finally the author analyzes the perspectives and tendencies of development of the international private space law.